Human alpha cell transcriptomic signatures of types 1 and 2 diabetes highlight disease-specific dysfunction pathways - Emanuele Bosi; Piero Marchetti; Guy Allen Rutter; Decio Laks Eizirik (iScience, 2022)
Summary: Although glucagon secretion is perturbed in both T1D and T2D, the pathophysiological changes in individual pancreatic alpha cells are still obscure. Using recently curated single-cell RNASeq data from T1D or T2D donors and their controls, we identified alpha cell transcriptomic alterations consistent with both common and discrete pathways. Although alterations in alpha cell identity gene (ARX, MAFB) expression were conserved, cytokine-regulated genes and genes involved in glucagon biosynthesis and processing were up-regulated in T1D. Conversely, mitochondrial genes associated with ROS (COX7B, NQO2) were dysregulated in T2D. Additionally, T1D alpha cells displayed altered expression of autoimmune-induced ER stress genes (ERLEC1, HSP90), whilst those from T2D subjects showed modified glycolytic and citrate cycle gene (LDHA?, PDHB, PDK4) expression. Thus, despite conserved alterations related to loss of function, alpha cells display disease-specific gene signatures which may be secondary to the main pathogenic events in each disease, namely immune- or metabolism-mediated-stress, in T1D and T2D, respectively.